Clinical and epidemiological characteristics of patients with Amyotrophic Lateral Sclerosis (ALS) in central Brazil - Bento, Dhiogo da Cruz Pereira; Oliveira, Rayana Pereira Dantas de; Santos, Kamilla de Faria; Azevedo, Rômulo Morais; Minasi, Lays Bernardes; Ternes, Yves Mauro Fernandes; Reis, Angela Adamski da Silva; Santos, Rodrigo da Silva (Medicina (Ribeirao Preto), 2022)
Objective: This study aimed to evaluate the clinical-epidemiological characteristics of patients with Amyotrophic Lateral Sclerosis (ALS) in the State of Goiás, Brazil. Methods: We conducted a descriptive cross-sectional study to assess medical records of patients with ALS followed-up at the State Rehabilitation and Readaptation Medical Center Dr. Henrique Santillo, Goiânia, GO, Brazil, between 2005 and 2018. In addition, we registered and created a photographic panel with the main clinical findings of ALS cases. Results: From 224 investigated patients, 51.8% were male, and 67.4% manifested the classic form of the disease. Initial symptoms were more frequent in the lower limbs (37.9%), and complications resulted in 45.5% of tracheostomy, 60.3% of gastrostomy, and 49.1% of deaths. Most patients had a five-year survival from the onset of symptoms, and no significant association between the use of non-invasive ventilation and increased survival were found. The analysis of the clinical-epidemiological characteristics showed a more extended time between the first symptoms and the diagnosis of the disease was observed. Conclusion: In this study, the time between the first symptoms and diagnosis was longer than in the literature, resulting in late treatments. In addition, there was no satisfactory result regarding survival with the use of non-invasive ventilation. Therefore, clinical-epidemiological studies of the disease in Brazil, as well as public awareness and training of professionals in recognition of ALS clinical signs will assist in early and more efficient interventions.